1994
DOI: 10.2307/3235864
|View full text |Cite
|
Sign up to set email alerts
|

Effects of removal of organic matter on the productivity of heathlands

Abstract: Abstract. Effects of milling, mowing and sod cutting on productivity in a Deschampsia grass heath and a Molinia‐Deschampsia grass heath were studied from 1977 to 1986. The sum of above‐ground biomass, litter and accumulated humified matter (TOM) in both types was ca. 70 ton/ha and the primary productivity 3–5 ton ha‐1yr‐1. Mulching did not affect the annual production. Sod cutting reduced the productivity to 1–2 ton ha‐1yr‐1; on the Molinia‐Deschampsia site this reduction lasted for at least a decade, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…This was consistent with the results from others (e.g. Berendse 1990;Aerts & Heil 1993;Diemont 1994;Snow & Marrs 1997) and it was concluded that turf cutting successfully restored oligotrophic conditions. However, germination and establishment of A. montana are negatively correlated with turf cutting depth.…”
Section: Discussionsupporting
confidence: 93%
“…This was consistent with the results from others (e.g. Berendse 1990;Aerts & Heil 1993;Diemont 1994;Snow & Marrs 1997) and it was concluded that turf cutting successfully restored oligotrophic conditions. However, germination and establishment of A. montana are negatively correlated with turf cutting depth.…”
Section: Discussionsupporting
confidence: 93%
“…Both turf‐stripping and rotavating cause significant disturbance to the soil and require plants establishing in the gaps created to regenerate either from seed or vegetatively from plant parts left at the new surface. Turf‐stripping removes soil organic matter, creating low nutrient conditions, which Dutch workers have suggested can favour the establishment of Calluna (Diemont & Linthorst Homan 1989; Diemont 1994), while rotavating may result in a pulse of nutrients released from decaying plant parts.…”
Section: Discussionmentioning
confidence: 99%
“…Soil disturbance by rotavation or ploughing has similar advantages and disadvantages but with generally lower efficacy. A Dutch experiment showed such treatments to be ineffective at returning degraded grass-dominated heath to dwarf-shrub domination although overall productivity was reduced (Diemont and Linthorst Homan, 1989;Diemont, 1994). As many species of high conservation value are likely to have few local sources of propagules and may have limited dispersal ability, direct planting combined with weed control may be required to avoid dominance by common ruderal species.…”
Section: Impacts On Habitat Suitabilitymentioning
confidence: 95%
“…As a large proportion of deposited N is retained in vegetation and in the upper layers of organo-mineral soils, it is clear that sod cutting is a very effective means to remove N from the system and may reduce N mineralisation rates and plant productivity for considerable periods of time (Berendse, 1990;Diemont, 1994;Heil and Bobbink, 1993) (see Tables 1 and 2). In one lowland heath the nutrient removal by sod cutting was equivalent to roughly 176 years of atmospheric deposition (Härdtle et al, 2006) which is likely to be much greater than removal by less-intensive management options (Härdtle et al, 2006.…”
Section: Impacts On N Removal and N Cyclingmentioning
confidence: 98%